PENGARUH PENGETAHUAN, KEMAMPUAN DAN PENGALAMAN KERJA TERHADAP KINERJA KARYAWAN PADA PT. HILON SUMATERA - Padang, Nomisari Riahna Karina; Sihombing, Sarimonang (UNIKA Santo Thomas, 2020)
The purpose of this study is to determine the effect of knowledge, abilities, and work experience towards employee performance at PT. Hilon Sumatera. The analytical method used is multiple linear regression analysis. The amount of population in this study is 53 people. The sampling method used is by doing census so that the amount of samples is also 53 people. The data was collected by using questionnaire, interview, and documentation study. From the result of the research, it is discovered that the coefficient of determination (R Square) is 0,593 or 59,3%. This means that the variations in employee working performance can be determined by variations in organizational commitment and working discipline by 59,3%, while the rest 40,7% is determined by other variables not included in this research, such as motivation, working discipline, morale, supervision, and leadership method. The multiple linear regression equation obtained from the data processing result is Y=6,161+0,346X1+0,286X2+0,186X3+ ei, which means that knowledge, abilities, and working experience are positively affecting the employee performance at PT. Hilon Sumatera. Hypothesis testing simultaneously shows that knowledge, abilities, and working experience are having a significant effect towards employee performance at PT. Hilon Sumatera. Partial Hypothesis Test (T Test) shows that knowledge has a positive and significant effect on employee performance, with a significance level of 0,000 < Î± (0,05), ability with a significance level of 0,005>Î± (0,05), and working experience with a significance level of 0,013< Î± (0,05). Refering to the results of this study, it is reccomended that PT. Hilon Sumatera should develop and maintain the indicators that are available on knowledge, abilites, and working experience.